Anglicism as a source of language neologization - Jehad, Ahmed Zuhair Mahmoud; ALI, HISHAM ALI HUSSEIN (Al-Adab Journal, 2022)
One of the actively developing branches of lexicology is neology, the object of its study is a new word or neologism. The task of neology is to identify new words and new meanings for words already existing in the language, analyze the causes and ways of their appearance, describe the factors that influence the emergence of a new language in the lexical system, and develop a language policy regarding new nominations. Neography deals with the lexicographic description of neologisms.In Russian studies, an active study of neologisms began in the second half of the 20th century, but interest in new nominations in the language appeared much earlier. For the first time, the definition of the term neologism was given in the "Desk Dictionary for References in All Branches of Knowledge" ed. F. Tollya (1864): “Neologism (Greek), the passion to introduce useless words into the language, i.e. designed to express ideas that are clearly conveyed by other words that have already come into use" [Alatortseva, 1999 p. 11]. The very word neologism was used earlier, for example, P. YaVyazemsky writes: “I will allow myself neologisms, i.e. additions to the Dictionary of the Russian Academy" [ibid., p. 11].